Knowledge capital : how knowledge-based enterprises really get built - Chatzkel, Jay L. (Oxford University Press, 2003)
Knowledge Capital: How Knowledge-Based Enterprises Really Get Built is an integrated, structured set of conversations with thought leaders and key practitioners in the fields of intellectual capital and knowledge management, who examine-in the form of conversations-the steps necessary for creating and implementing the various dimensions of a knowledge-based enterprise. These are the dimensions that need to be effectively addressed for the organization to successfully make the transition from an activity-based organization to a truly knowledge-based enterprise. The conversations that make up Knowledge Capital are not studies of theory separated from practice or practice without a strong theoretical base. Rather, they are the stories of how knowledge-based enterprises really get built, in the words of the people who built them. While every contributor begins from his or her own unique perspective and background, each moves toward a convergent understanding of the core elements, perspectives, and practices involved.; These systemic conversations provide a body of knowledge and experience on how to craft and implement strategies, as well as the how values, learning, performance, relationships, innovation, and change play in the development of usable knowledge environment. These explorations, together, lead to a mapping of what are quickly becoming the foundations of the next stage of the field. Knowledge Capital gives the reader a readily accessible collection of insights and experiences essential for the new era in intellectual capital and knowledge management.